High-entropy alloy slurry for vacuum cladding and preparation method of high-entropy alloy coating of high-entropy alloy slurry

Through vacuum cladding and sintering method, high-entropy alloy paste is used to prepare coatings on the surface of complex workpieces of titanium and titanium alloys, solving the problems of high equipment costs and limited coating thickness in the existing technology, and achieving high hardness and corrosion resistance and high temperature resistance coatings reduce production costs and improve reliability.

CN119187554AActive Publication Date: 2024-12-27Liupanshan Laboratory

Patent Information

Application Number
CN202411369822.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The prior art has problems such as high equipment cost, cracking risk, limited coating thickness, and difficulty in molten pool control when preparing high-entropy alloy coatings on the surface of complex workpieces of titanium and titanium alloys. It is difficult to achieve high hardness, corrosion resistance and high temperature oxidation resistance. Performance coating.

Method used

Using high-entropy alloy slurry for vacuum cladding, through the vacuum cladding sintering method after slurry, the four major effects of high-entropy alloys are used to prepare uniform and dense thermally protective high-entropy alloy coatings, reducing production costs and improving reliability .

Benefits of technology

It significantly improves the hardness, corrosion resistance and high temperature resistance of the coating, reduces production costs, and is simple in process and simple in equipment, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses high-entropy alloy slurry for vacuum cladding and a preparation method of a high-entropy alloy coating of the high-entropy alloy slurry. The uniform and compact thermal protection high-entropy alloy coating can be formed on the surfaces of titanium and titanium alloy by utilizing four effects of the high-entropy alloy and adopting a slurry hanging sintering process, so that the service life of the titanium and titanium alloy coating in a high-temperature and corrosive environment is remarkably prolonged, and the reliability of the titanium and titanium alloy coating in the high-temperature and corrosive environment is remarkably improved. The high-entropy alloy slurry is composed of Mo powder, Cr powder, Fe powder, Co powder, Ni powder and B powder, and polyethylene glycol, acetylated hydroxy propyl cellulose, epoxy resin and absolute ethyl alcohol serve as binders. The specific preparation method comprises the following steps: preparing powder and a binder in proportion, mixing the alloy powder with the binder after ball milling, carrying out sand blasting treatment on a sample, hanging slurry, drying, carrying out vacuum cladding sintering and the like. The process is simple and easy to implement, low in equipment requirement, controllable in coating thickness, high in binding force, good in mechanical property and corrosion resistance and suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface modification of metallic titanium and titanium alloy materials, and particularly relates to a method for preparing a high entropy alloy slurry for vacuum cladding and a high entropy alloy coating thereof. Background Art

[0002] Titanium alloys are widely used in the aerospace industry, mainly due to their high corrosion resistance, high strength and high temperature resistance. Due to these characteristics, titanium alloys have become ideal materials for manufacturing aircraft and spacecraft components. Especially in Western countries, such as the United States, 60% of titanium is used in this field. Asian countries, such as Japan and China, also use about 10% of titanium in this field. With the rapid development of the Asian aviation industry, the consumption of titanium is expected to grow further. In general, the aviation industry has a decisive influence on the titanium market, and the application of titanium alloys has also promoted the advancement of aviation technology.

[0003] Titanium alloy has an extremely high strength-to-weight ratio. Its strength is comparable to that of steel, but its weight is only about half of that of steel. It exhibits excellent corrosion resistance in various harsh environments, especially in seawater, salt spray and fuel. This corrosion resistance extends the service life of aircraft and spacecraft and reduces maintenance costs and frequency. In the aerospace field, titanium alloy has a low coefficient of thermal expansion and good compatibility with composite materials and other high-performance materials, which helps to reduce stress and deformation caused by thermal expansion and ensure the stability and reliability of aircraft structures. At the same time, the biocompatibility of titanium alloy makes it non-toxic both inside and outside the human body, making it suitable for the manufacture of astronaut equipment and life support systems.

[0004] However, there are problems with insufficient oxidation resistance, wear resistance and corrosion resistance during the use of titanium alloys. The oxidation resistance of titanium alloys at high temperatures is not as good as that of some other high-temperature alloys. Although a dense oxide film can be formed in the air to protect its internal materials, this oxide film may break under high temperature conditions, making the titanium alloy susceptible to further oxidation corrosion, which limits the application of titanium alloys under extreme high temperature conditions. The hardness and wear resistance of titanium alloys are relatively low, and they are easily worn under friction and impact. Although its wear resistance can be improved by surface treatment such as nitriding, oxidation, coating and other methods, these treatments increase the manufacturing and maintenance costs of the material. In high-stress or high-wear environments, such as gears, bearings and other components, titanium alloys may need to be used in combination with other materials to make up for their lack of wear resistance. In addition, in certain specific corrosive environments (such as chloride-containing environments), problems such as stress corrosion cracking (SCC) and hydrogen embrittlement are exhibited.

[0005] Therefore, surface modification research, that is, the preparation of coatings or surface protective films on the surface of titanium and titanium alloys, has become a current research hotspot. High entropy alloys have unique elemental composition, arrangement and interaction potential field. Scholars summarize the characteristics of high entropy alloys into "four major effects", namely, high entropy effect in thermodynamics, lattice distortion effect in structure, hysteresis diffusion effect in kinetics and "cocktail" effect in properties. High entropy alloys have excellent corrosion resistance due to their unique multi-element composition and solid solution structure. The mutual solubility of different elements and high mixing entropy effect help to inhibit the formation of intermetallic compounds, so that the coating has a more uniform and stable chemical composition, thereby showing better corrosion resistance in corrosive media. Since high entropy alloy coatings contain a variety of high-temperature resistant elements, such as chromium (Cr), nickel (Ni) and aluminum (Al), these elements can form a stable oxide protective film at high temperatures, thereby significantly improving the oxidation resistance of the coating. The high entropy effect and slow diffusion effect give high entropy alloy coatings excellent thermal stability and uniformity. The coating will not undergo significant phase changes or element segregation at high temperatures, thereby ensuring its performance stability in complex environments.

[0006] At present, common methods for preparing high-entropy alloy coatings include thermal spraying, laser cladding, magnetron sputtering, electrodeposition, and plasma cladding. These technologies have more or less limiting factors: magnetron sputtering is inefficient and takes a long time to prepare the coating; thermal spraying has high porosity and may have weak bonding; electrodeposition is difficult to control the composition, which may lead to uneven coating composition and limited thickness.

[0007] Chinese patents CN 117344306 A, CN 108103494 A, CN 118531393 A and CN 106319513 A all use laser cladding to prepare high entropy alloy coatings of different systems. Laser cladding has the following disadvantages: 1. High equipment cost: Laser cladding systems usually require high-performance lasers, precision motion platforms and supporting powder feeding equipment, and the purchase and maintenance costs of these equipment are relatively high. 2. There is a risk of cracking: During the laser cladding process, thermal stress may be generated inside the coating due to rapid cooling caused by high energy density. This stress is more obvious when the coating thickness is large, which can easily cause the coating to crack or crack, affecting the performance and service life of the coating. 3. Limited coating thickness: Laser cladding is suitable for preparing thin coatings, usually between a few hundred microns and a few millimeters. Too thick a coating will cause deformation of the substrate due to concentrated thermal stress, affecting the overall quality of the coating and reducing its application effect. 4. Difficulty in controlling the molten pool: During the laser cladding process, the stability of the molten pool is crucial. The temperature, shape and flow state of the molten pool need to be precisely controlled, and any instability will lead to defects such as uneven coating thickness, pores or inclusions. It is difficult to control the porosity of the coating using this process and it is difficult to ensure the quality of the coating.

[0008] Chinese patent CN 103556146 A uses an organic solvent to mix with 200 mesh metal Fe, Cr, Cu, Ni, Co, Mn, and Mo powders, and uses tungsten inert gas welding to clad the alloy powder on the substrate surface. Although tungsten inert gas welding (TIG) cladding has good quality, it also has disadvantages: 1. Slow cladding speed: The welding speed of TIG welding is relatively low, especially when the cladding thickness requirement is large, which may lead to reduced production efficiency. 2. High heat input: Due to the long residence time required during the welding process, the heat input is relatively high, which may cause overheating, deformation of the substrate or structural changes in the heat-affected zone. 3. High operating requirements: TIG welding requires high skills from the operator and requires experienced welders to ensure welding quality, especially in the control of welding parameters during the cladding process. 4. High material cost: TIG welding often uses high-priced welding materials (such as high-purity tungsten electrodes and specific welding wires), which increases the overall material cost. It is difficult to meet the demand for large quantities of products using this method, and there is process instability.

[0009] How to simply and efficiently prepare a coating with high hardness, corrosion resistance, wear resistance and high-temperature oxidation resistance on the surface of complex titanium and titanium alloy workpieces is a technical problem to be solved by the present invention. Summary of the invention

[0010] The purpose of the present invention is to provide a high entropy alloy slurry for vacuum cladding and a method for preparing a high entropy alloy coating on the surface of titanium or titanium alloy in view of the problems existing in the prior art. By utilizing the four major effects of high entropy alloys, a uniform and dense thermal protection high entropy alloy coating can be prepared on the surface of titanium and titanium alloy complex workpieces through a method of vacuum cladding and sintering after slurry hanging, thereby significantly improving its service life and reliability in high temperature and corrosive environments, and greatly reducing production costs. The method also has the advantages of simple operation, simple required equipment, reliable and stable process, and can realize industrial production. The coating obtained by this method has high hardness, uniform structure, low porosity and controllable coating thickness.

[0011] To achieve the above purpose, the technical solution adopted by the present invention is as follows: The present invention first provides a high entropy alloy slurry for vacuum cladding, which is composed of high entropy alloy powder and a binder. The high entropy alloy powder is composed of 3-4 at.% B, 22-24 at.% Cr, 23-25 ​​at.% Fe, 2.5-3.5 at.% Mo, 11-13 at.% Co, and the rest is Ni. The binder is composed of 1-5 wt.% polyethylene glycol, 1-5 wt.% acetylated hydroxypropyl cellulose, 1-2 wt.% epoxy resin, and the rest is anhydrous ethanol.

[0012] In the above technical solution, B, Cr, Fe, Mo, Co, and Ni in the high entropy alloy powder are provided by B, Cr, Fe, Mo, Co, and Ni metal element powders, wherein the purity of Mo, Cr, Fe, B, Co, and Ni powders are all analytically pure, and the powder particle size is all less than 100 microns.

[0013] In the above technical solution, the number average molecular weight Mn of the polyethylene glycol in the binder is 6000-20000, preferably Mn is 20000; the epoxy equivalent of the epoxy resin is 180-200 g / eq.

[0014] Furthermore, the slurry composition is: 85 wt.% of high entropy alloy powder and 15 wt.% of binder.

[0015] The present invention further provides a method for preparing the high entropy alloy slurry for vacuum cladding, comprising the following steps: (1) weighing Mo, Cr, Fe, Co, Ni, and B metal powders according to atomic ratio, placing the powders in a ball mill for 15 h at a speed of 350-420 rpm, and then pouring out for later use to obtain high entropy alloy powders; (2) polyethylene glycol, acetylated hydroxypropyl cellulose, epoxy resin and anhydrous ethanol were weighed and mixed according to the binder formula, and then ball-milled in a ball mill for 1 h at a ball-milling speed of 300 rpm to obtain a binder; (3) The high entropy alloy powder and the binder are mixed in proportion and mechanically stirred to obtain a high entropy alloy slurry.

[0016] The present invention also provides a method for preparing a high entropy alloy coating on a titanium / titanium alloy surface by using the high entropy alloy slurry for vacuum cladding, wherein the coating is prepared by using the high entropy alloy slurry for vacuum cladding and sintering, and the method comprises the following steps: (1) Sample pretreatment: The titanium / titanium alloy samples were sandblasted to remove surface impurities and increase surface roughness to promote the adhesion of the coating. The sandblasted samples were cleaned with anhydrous ethanol and dried to ensure that the surface was clean and free of oil stains.

[0017] (2) Slurry coating: immerse the sample pretreated in step (1) into the prepared high entropy alloy slurry and gently stir for 10-15 seconds to ensure that the sample surface is evenly coated with slurry; in order to increase the coating thickness, the sample after slurry coating can be uniformly dried in a vacuum drying oven at 500°C for 70-80 minutes, and then cooled to 50°C; the binder ratio remains unchanged, and secondary slurry coating or repeated slurry coating is performed, and the slurry coating thickness is 1.5-2.2 mm, and the preferred slurry coating thickness is 2 mm.

[0018] (4) Drying: Place the coated sample in a drying oven and keep it at 500°C for 70 minutes to allow the coating to dry completely and the residual gas after thermal decomposition of organic matter in the coating to completely escape.

[0019] (5) Vacuum cladding sintering: Place the dried sample in a vacuum sintering furnace and keep it at 1320-1360°C for 40-60 minutes. This step helps to form a good metallurgical bond between the coating and the substrate, improving the mechanical properties and corrosion resistance of the coating. Subsequently, the sample is cooled with the furnace. After the vacuum sintering furnace is cooled to 50°C, the sample is taken out and the residue on the surface of the sample is rinsed with running water, then cleaned again with anhydrous ethanol, and finally dried to obtain the final high entropy alloy coating.

[0020] Furthermore, the vacuum degree of the vacuum cladding sintering is 10 -4 Below Pa.

[0021] Furthermore, the heating rate of the vacuum cladding sintering is 5-10°C / min, specifically, the heating rate is 10°C / min within the temperature range of 50-500°C, the heating rate is 8°C / min within the temperature range of 500-1000°C, and the heating rate is 5°C / min above 1000°C.

[0022] Beneficial effects of the present invention: The present invention first designs a MoCrFeCoNiB high entropy alloy powder, and improves the corrosion resistance and wear resistance of the coating by adjusting the element dosage.

[0023] As the Cr content gradually increases from a low content (such as 5%), the corrosion resistance will be significantly improved. This is because Cr can form a stable passivation film (such as Cr2O3), which effectively prevents matrix corrosion. At the same time, the high-temperature strength usually increases gradually, and Cr can enhance the stability of the alloy at high temperatures. After reaching a certain Cr content (usually between 15% and 25%), the corrosion resistance will tend to saturation, and the effect of further increasing the Cr content will weaken. At extremely high Cr contents, the structure of the alloy may become fragile, affecting the corrosion resistance, and the high-temperature strength will also decrease.

[0024] The presence of Fe helps stabilize the formation of FCC or BCC phases and improves the structural stability of the alloy. The recommended range is 15-25%. When the Fe content gradually increases from a low content (such as 10%), the structural stability of the alloy is usually enhanced. Within the moderate range of 15-30%, the increase in Fe will continue to improve the structural stability and enhance the durability and deformation resistance of the alloy. Once the iron content exceeds the threshold of 30%, the alloy may undergo phase transformation or increase brittleness, resulting in a decrease in structural stability.

[0025] Co maintains strength and hardness in high temperature environments and is an important element in high-temperature alloys. As the Co content gradually increases from a low content (such as 5%), the strength and hardness of the alloy usually increase significantly. Co can enhance the high-temperature strength and toughness of the alloy and improve its mechanical properties. In the medium range of 5-15%, the strength and hardness usually continue to increase, and the increase in Co helps to improve the structural stability of the alloy. When the Co content reaches a certain threshold (usually between 15% and 20%), the strength and hardness may reach a peak, at which point the effect of further increasing the Co content on performance improvement is weakened. At extremely high Co contents (such as more than 20%), increased brittleness or phase transformation may occur, resulting in a decrease in strength and hardness.

[0026] When the Ni content is gradually increased from a low content (such as 10%), the ductility will increase significantly. This is because Ni can stabilize the FCC structure and enhance the toughness of the alloy. Ductility may reach a peak in the 15-20% content range. At this point, the microstructure of the alloy has been optimized, and the toughness and ductility have been significantly enhanced. When the content exceeds 20%, ductility may begin to decrease. This is because excessive Ni may cause phase transformation, lattice distortion or interaction in the alloy, affecting the overall mechanical properties of the alloy.

[0027] B can significantly refine the grains and improve the comprehensive mechanical properties of the alloy. As the B content increases from 0.5% to 4%, the grain size of the alloy usually decreases significantly. The addition of B can promote the formation of crystal nuclei, thereby effectively refining the grains. In the range of 0.5%-4%, the grain refinement effect is most obvious. At this time, the refined grains can improve the mechanical properties of the alloy, such as strength and toughness. When the B content further increases to more than 4%, the grain refinement effect may tend to saturation, and the degree of refinement will no longer increase significantly. At very high B contents (more than 5%), it may cause grain growth or the production of other phases, which in turn affects the microstructural stability of the alloy.

[0028] The addition of Mo element can refine the microstructure of the alloy and form a mixed phase structure of FCC phase and σ phase. As the Mo content increases from 5% to 15%, the microstructure of the alloy is usually significantly refined. Mo can promote phase transformation and nucleation, which helps to improve the uniformity and refinement of grains. When the Mo content is increased in the initial stage, the hardness of the alloy is usually significantly improved. When the Mo content reaches between 15-20%, the refinement effect and the improvement of hardness may tend to saturation, and the effect of further increasing the Mo content on performance improvement is weakened. However, excessive Mo may cause Cr precipitation, affecting the overall performance of the alloy. Excessive Mo may cause uneven organization, affect the phase stability of Fe, and thus affect the toughness of the alloy. In addition, excessive Mo may interfere with the solid solution strengthening effect of B and affect the overall structural stability of the alloy. In order to achieve better results, we control the Mo content within 5-10%.

[0029] Combining the chemical composition of high entropy alloy powder and substrate, the present invention designs a binder, in which polyethylene glycol has good lubrication properties, can reduce friction between materials, improve the processing performance of materials during the preparation process, and can give materials a certain flexibility, enhance the toughness and crack resistance of the coating. Acetylated hydroxypropyl cellulose is a commonly used thickener, which can significantly increase the viscosity of the slurry and prevent the sedimentation of dispersed particles. It has good film-forming properties and can form a uniform film layer after the coating dries, enhancing the density and durability of the coating. Varnish has good adhesion and can form a protective film on the surface to prevent the external environment from eroding the coating and improve corrosion resistance. Acetylated hydroxypropyl cellulose as a thickener, combined with polyethylene glycol, can prevent particle sedimentation and maintain uniform distribution of the slurry; at the same time, the adhesion of the varnish ensures the firm adhesion of the coating on the substrate. The combination of the three can provide better adhesion and ensure the stability and uniformity of the coating during the preparation process.

[0030] The present invention mixes MoCrFeCoNiB high entropy alloy powder with a specific binder to prepare a slurry, and the method of preparing a coating on a complex surface of titanium and titanium alloy by slurry sintering using the high entropy alloy slurry has significant advantages in terms of equipment cost, process simplicity, coating quality and bonding strength. The required equipment is relatively simple, and no high-cost laser or vacuum system is required, which greatly reduces the operation and maintenance costs. It is easy to mass produce, the coating thickness is controllable, and the production efficiency is high. The preparation efficiency of the high entropy alloy coating is significantly improved, and the utilization efficiency of the powder is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The surface morphology of the coating after drying (left) and vacuum cladding (right) in Example 4; Figure 2The surface morphology of the coating after drying (left) and vacuum cladding (right) in Example 5; Figure 3 The surface morphology of the coating after drying (left) and vacuum cladding (right) in Example 6; Figure 4 This is the EDS characterization spectrum of the high entropy alloy coating prepared in Example 4; Figure 5 This is the EDS characterization spectrum of the high entropy alloy coating prepared in Example 5; Figure 6 This is the EDS characterization spectrum of the high entropy alloy coating prepared in Example 6; Figure 7 This is the morphology of the interface area of ​​the high entropy alloy coating prepared in Example 6; Figure 8 This is the XRD characterization spectrum of the high entropy alloy coating prepared in Example 6. DETAILED DESCRIPTION

[0032] The present invention is described in detail below with reference to the embodiments.

[0033] The raw materials used in the following specific embodiments of the present invention are as follows: The substrate material is Ti-6Al-4V (Grade 5).

[0034] Cobalt (Co) powder (99.9%), particle size <10 μm, was purchased from Sigma-Aldrich.

[0035] Chromium (Cr) powder (99.5%), particle size <20 μm, was purchased from Alfa Aesar.

[0036] Iron (Fe) powder (99.9%), particle size <10 μm, was purchased from Merck.

[0037] Molybdenum (Mo) powder (99.5%), particle size <15 μm, was purchased from Alfa Aesar.

[0038] Nickel (Ni) powder (99.8%), particle size < 30 μm, was purchased from Alfa Aesar.

[0039] Boron (B) powder (99.5%), particle size < 48 μm, was purchased from Alfa Aesar.

[0040] Polyethylene glycol (Mn 20000) was purchased from aladdin.

[0041] Epoxy resin (EPON Resin 828), viscosity 110-150 P, purchased from Hexion.

[0042] The raw materials and reagents not specifically described in the present invention can all be obtained commercially. Example 1

[0043] The high entropy alloy powder composition is: 3at. % B powder, 22at. % Cr powder, 23at. % Fe powder, 2.5at. % Mo powder, 11at. % Co powder, and 38.5at. % Ni powder.

[0044] The metal powder was put into a ball mill for ball milling, with a ball-to-material ratio of 15:1. The grinding balls used were zirconia ceramic balls, with large balls, medium balls and small balls in a ratio of 3:5:2. The ball mill speed was 450 r / min and the ball milling time was 13 h. The ball-milled powder was pressed into a 10*10*10mm block, and the sample was prepared for metallographic microscope observation. The obtained high entropy alloy powder had good uniformity, the crystal phase mainly remained the initial phase, the particle size was small, and no obvious phase change occurred. Example 2

[0045] The difference between this embodiment and embodiment 1 is that the ball mill speed is 300 r / min and the ball milling time is 18 h. Metallographic microscopic observation shows that the powder particle size is reduced and part of the crystal phase is transformed into an unstable phase, resulting in a decrease in the performance of the material. Example 3

[0046] The difference between this embodiment and embodiment 1 is that the ball mill speed is 330 r / min and the ball milling time is 15 h. Metallographic microscopic observation shows that the powder particle size is moderate, the crystal phase remains stable, and good physical and chemical properties are obtained. Continuing to increase the ball mill speed under this ball milling time can obtain a smaller powder particle size while ensuring that the crystal phase does not change. Example 4

[0047] (1) Sample pretreatment: The sample was sandblasted and then cleaned and dried with anhydrous ethanol; (2) Preparation of slurry: The high entropy alloy powder composition is: 3at. % B powder, 22at. % Cr powder, 23at. % Fe powder, 2.5at. % Mo powder, 11at. % Co powder, 38.5at. % Ni powder. The prepared powder is placed in a ball mill and ground for 15 h at a speed of 350 r / min, and then taken out for use. The binder composition is: 3wt. % polyethylene glycol, 1% acetylated hydroxypropyl cellulose, 1% epoxy resin, and the rest is anhydrous ethanol. The prepared binder is placed in a ball mill and ground for 1 h at a speed of 300 r / min, and then taken out for use. The slurry composition is: 85wt. % high entropy alloy powder, 15wt. % binder.

[0048] (3) Slurry coating: immerse the titanium alloy into the slurry, stir it slightly, and take it out after 10 seconds. The slurry coating thickness is 1.5 mm; (4) Drying: Place the coated sample in a vacuum drying oven and keep it at 500°C for 70 min to fully dry the coating and prevent bubbles during the sintering process; (5) Vacuum cladding sintering: The dried sample is placed in a vacuum sintering furnace and kept at 1320°C for 40 min. The sample is cooled along with the furnace. After the vacuum sintering furnace is cooled to 50°C, the sample is taken out and cleaned with anhydrous ethanol, and then dried to obtain a high-entropy alloy coating. Example 5

[0049] (1) Sample pretreatment: The sample was sandblasted and then cleaned with anhydrous ethanol and dried; (2) Preparation of slurry: The high entropy alloy powder composition is: 3at. % B powder, 23at. % Cr powder, 24at. % Fe powder, 3% Mo powder, 12at. % Co powder, 35at. % Ni powder. The prepared powder is placed in a ball mill and ground for 15 h at a speed of 390 r / min, and then taken out for use. The binder composition is: 4% polyethylene glycol, 3% acetylated hydroxypropyl cellulose, 1% epoxy resin, and the rest is anhydrous ethanol. The prepared binder is placed in a ball mill and ground for 1 h at a speed of 300 r / min, and then taken out for use. The slurry composition is: 85wt. % high entropy alloy powder, 15wt. % binder.

[0050] (3) Slurry coating: immerse the titanium alloy into the slurry, stir it slightly, and take it out after 13 seconds. The slurry coating thickness is 1.8 mm. (4) Drying: Place the coated sample in a vacuum drying oven and keep it at 500°C for 70 min to fully dry the coating and prevent bubbles during the sintering process; (5) Vacuum cladding sintering: The dried sample is placed in a vacuum sintering furnace and kept at 1340°C for 50 min. The sample is cooled along with the furnace. After the vacuum sintering furnace is cooled to 50°C, the sample is taken out and cleaned with anhydrous ethanol, and then dried to obtain a high-entropy alloy coating. Example 6

[0051] (1) Sample pretreatment: The sample was sandblasted and then cleaned with anhydrous ethanol and dried; (2) Preparation of slurry: The high entropy alloy powder composition is: 4at.% B powder, 24at.% Cr powder, 25at.% Fe powder, 3.5at.% Mo powder, 13at.% Co powder, and the balance is Ni powder. The prepared powder is placed in a ball mill and ground for 15 h at a speed of 420 r / min, and then taken out for use. The binder composition is: 4% polyethylene glycol, 5% acetylated hydroxypropyl cellulose, 2% epoxy resin, and the rest is anhydrous ethanol. The prepared binder is placed in a ball mill and ground for 1 h at a speed of 300r / min, and then taken out for use. The slurry composition is: 85wt.% high entropy alloy powder, 15wt.% binder.

[0052] (3) Slurry coating: immerse the titanium alloy into the slurry, stir it slightly, and take it out after 15 seconds. The slurry coating thickness is about 2.1 mm; (4) Drying: Place the coated sample in a vacuum drying oven at 500°C for 70 min to fully dry the coating and prevent bubbles during the sintering process; (5) Vacuum cladding sintering: The dried sample is placed in a vacuum sintering furnace and kept at 1360°C for 60 min. The sample is cooled along with the furnace. After the vacuum sintering furnace is cooled to 50°C, the sample is taken out and cleaned with anhydrous ethanol, and then dried to obtain a high-entropy alloy coating.

[0053] Performance indicators and specific testing methods of the product of the present invention: The high entropy alloy coating prepared by the present invention has few micropores and no cracks, and the thickness of the coating after vacuum cladding and sintering is ≥1 mm. Taking Example 6 as an example, the cross section is observed after cutting, and 10 different areas at the interface and the coating are observed. The porosity of the coating is calculated using Image J software, and a maximum value and a minimum value are removed. The average value of the remaining data is taken to obtain a coating porosity of 1.86%, which is significantly lower than the coating porosity of the laser cladding process and the tungsten inert gas welding cladding process.

[0054] The high entropy alloy coating prepared by the present invention is mainly composed of FCC phase and σ phase. Through nanoindentation hardness test, it is found that the hardness of FCC phase is between 3.94-4.07 Gpa, while the hardness of σ phase region can reach 7.35 Gpa, the hardness of FCC + σ phase region can reach 5.82-6.23 Gpa, and the overall hardness of the alloy can reach between 7.79-8.14 Gpa. It is much higher than the hardness of titanium and titanium alloys. With the increase of Mo content, the hardness of the coating increases, which is related to the increase of σ phase area.

[0055] High temperature oxidation resistance: Use a muffle furnace for oxidation test: clean the coating and substrate samples, and remove surface contaminants (such as grease, dust, etc.). Measure the dimensions of the samples to ensure that the initial state of each sample is recorded. Place the sample in the muffle furnace and start heating at a heating rate of 8°C / min. Monitor the temperature changes in the furnace to ensure that the temperature rises steadily to 800°C. Maintain oxidation treatment at 800°C for 12 hours, and monitor the temperature regularly during this period to ensure stability. After the treatment, the sample is cooled in the muffle furnace. After the furnace temperature cools to room temperature, the sample is taken out for cross-sectional analysis to study whether the coating has failure behaviors such as cracking and peeling, and compare it with the substrate.

[0056] The corrosion resistance was tested comparatively using 3.5% NaCl solution and 4% HF solution. Prepare the coating sample (2×2cm), ensure that its surface is smooth and clean, and record the initial mass. The sample size should be consistent to ensure the comparability of the experiment. Immerse the sample completely in the NaCl solution and HF solution, respectively, and record the time when the immersion starts. Set the immersion time to 48 hours, and take out the sample after the time is up. After taking out the sample, wash it with deionized water to remove the surface salt and wipe it dry gently. Use a precision balance to measure the mass of each sample and record the mass change before and after immersion. Weight loss = initial mass − mass after immersion.

[0057] Table 1 Test results of high entropy alloy coating performance

[0058] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high entropy alloy slurry for vacuum cladding, characterized in that: The high entropy alloy slurry comprises, by mass percentage, 85 wt.% of high entropy alloy powder and 15 wt.% of a binder; the high entropy alloy powder is composed by atomic percentage of: B 3-4 at.%, Cr 22-24 at.%, Fe 23-25 ​​at.%, Mo 2.5-3.5 at.%, Co 11-13 at.%, and Ni balance; the binder is composed by mass percentage of: polyethylene glycol 1%-5%, acetylated hydroxypropyl cellulose 1%-5%, epoxy resin 1-2%, and the balance is anhydrous ethanol.

2. The high entropy alloy slurry for vacuum cladding according to claim 1, characterized in that: The Mo, Cr, Fe, B, Co and Ni elements in the high entropy alloy powder are provided by Mo, Cr, Fe, B, Co and Ni metal single substance powders respectively. The purity of the metal single substance powders is analytically pure and the powder particle size is less than 100 microns.

3. The high entropy alloy slurry for vacuum cladding according to claim 1, characterized in that: In the binder, the number average molecular weight of the polyethylene glycol is 6000-20000; and the epoxy equivalent of the epoxy resin is 180-200 g / eq.

4. The method for preparing a high entropy alloy slurry for vacuum cladding according to any one of claims 1 to 3, characterized in that: The steps include: (1) weighing Mo, Cr, Fe, Co, Ni, and B metal powders according to the atomic percentages, placing them in a ball mill and milling them for 15 hours at a speed of 350-420 rpm to obtain high entropy alloy powder; (2) weighing raw materials according to the weight percentage of the binder, mixing them, placing them in a ball mill for 1 hour at a ball milling speed of 300 rpm to obtain a binder; (3) The high entropy alloy powder and the binder are mixed in proportion and mechanically stirred to obtain the high entropy alloy slurry for vacuum cladding.

5. A method for preparing a high entropy alloy coating, characterized in that: The steps include: (1) Sample pretreatment: sandblast the sample, clean and dry it; (2) Slurry coating: immersing the sample pretreated in step (1) into the high entropy alloy slurry for vacuum cladding according to any one of claims 1 to 3, and gently stirring to make the surface of the sample evenly coated with slurry; (3) Drying: Place the sample after slurry coating in a drying oven and keep it at 500°C for 70-80 minutes; (4) Vacuum cladding sintering: The dried sample is placed in a vacuum sintering furnace and kept at 1320-1360°C for 40-60 min. The sample is cooled along with the furnace. After the temperature drops to 50°C, the sample is taken out, cleaned, and dried to obtain a high entropy alloy coating.

6. The method for preparing a high entropy alloy coating according to claim 5, characterized in that: The slurry coating thickness in step (2) is 1.5-2.2 mm.

7. The method for preparing a high entropy alloy coating according to claim 5, characterized in that: The slurry coating in step (2) further includes drying the sample at 500° C. for 70-80 minutes after slurry coating, cooling the sample to below 50° C., and then repeatedly slurry coating to increase the slurry coating thickness.

8. The method for preparing a high entropy alloy coating according to claim 5, characterized in that: The vacuum degree of the vacuum cladding sintering is less than 10 -4 Pa, the heating rate of the vacuum cladding sintering is 5-10°C / min.

9. The method for preparing a high entropy alloy coating according to claim 8, characterized in that: The vacuum cladding sintering has a heating rate of 10°C / min at a temperature of 50-500°C; a heating rate of 8°C / min at a temperature of 500-1000°C; and a heating rate of 5°C / min at a temperature above 1000°C.

10. The method for preparing a high entropy alloy coating according to claim 5, characterized in that: The material of the sample is titanium or titanium alloy.

Citation Information

Patent Citations

  • Fracturing pump valve body and valve seat vacuum fusion covering surface strengthening method

    CN104162676A

  • High-entropy alloy coating material and preparation method thereof

    CN105624515A

  • Method for preparing superhard Ti10CoCrNiFeNbx high-entropy alloy coating on surface of high-purity titanium

    CN110344052A

  • Self-fluxing high-entropy alloy powder and preparation and application methods thereof

    CN115094294A

  • Preparation method of high-entropy alloy coating material with high wear resistance and corrosion resistance

    CN115555569A

Cited By

  • Laser cladding high-entropy alloy carbide ceramic coating and preparation method thereof

    CN120924967A